Deep sequencing reveals the first fabavirus infecting peach - He, Yan (Sci Rep, 2017)
A disease causing smaller and cracked fruit affects peach [Prunus persica (L.) Batsch], resulting in significant decreases in yield and quality. In this study, peach tree leaves showing typical symptoms were subjected to deep sequencing of small RNAs for a complete survey of presumed causal viral pathogens. The results revealed two known viroids (Hop stunt viroid and Peach latent mosaic viroid), two known viruses (Apple chlorotic leaf spot trichovirus and Plum bark necrosis stem pitting-associated virus) and a novel virus provisionally named Peach leaf pitting-associated virus (PLPaV). Phylogenetic analysis based on RNA-dependent RNA polymerase placed PLPaV into a separate cluster under the genus Fabavirus in the family Secoviridae. The genome consists of two positive-sense single-stranded RNAs, i.e., RNA1 [6,357 nt, with a 48-nt poly(A) tail] and RNA2 [3,862 nt, with a 25-nt poly(A) containing two cytosines]. Biological tests of GF305 peach indicator seedlings indicated a leaf-pitting symptom rather than the smaller and cracked fruit symptoms related to virus and viroid infection. To our knowledge, this is the first report of a fabavirus infecting peach. PLPaV presents several new molecular and biological features that are absent in other fabaviruses, contributing to an overall better understanding of fabaviruses.